STRATEGI PENGEMBANGAN CONTENT BASED VIDEO RETRIEVAL PADA PERPUSTAKAAN SEKOLAH TINGGI MULTI MEDIA MMTC YOGYAKARTA - Sri Wahyuni (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2021)
Utilization of knowledge, especially those in video format, sometimes librarians and users have problems finding collections based on video content. This paper aims to see how the strategy of developing Content Based Video Retrieval at the MMTC Yogyakarta Multi Media High School Library. The research method used by researchers using qualitative research with a library research approach. The data collection technique of this research begins with the activities of selecting, searching, presenting and finally analyzing the data. In analyzing the data, the researcher uses content analysis techniques (content analysis). is a research technique to make reference to the introduction of certain characteristics in the text systematically and objectively. The results showed that the development of the Yogyakarta MMTC Multi Media High School Library, especially for the development of a Video-Based Retrieval System (CBVR) must be evaluated through a SWOT analysis in two ways, namely macro analysis, opportunities and threats variables will be formulated, and second from internal analysis will be formulated strength variables. and weakness. In addition, in the Content Based Video Retrieval development strategy, there are aspects that need to be considered and seen, namely: user needs, development budget, human resources: library staff, support from leadership and facilities (software and hardware) and IT infrastructure (network).